2002
DOI: 10.1016/s0378-1097(02)00801-7
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected changes in photosystem I function in a cytochrome c6-deficient mutant of the cyanobacterium Synechocystis PCC 6803

Abstract: Cytochrome c 6 , the product of the petJ gene, is a photosynthetic electron carrier in cyanobacteria, which transfers electrons to photosystem I and which is synthesised under conditions of copper deficiency to functionally replace plastocyanin. The photosystem I photochemical activity (energy storage, photoinduced P700 redox changes) was examined in a petJ-null mutant of Synechocystis PCC 6803. Surprisingly, photosystem I activity in the petJ-null mutant grown in the absence of copper was not much affected. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…2). The c 6 cytochromes serve as electron donors to cytochrome c oxidase in cyanobacteria (2, 13) and transfer electrons from cytochrome b 6 f to photosystem I in both cyanobacteria and unicellular algae (2,13,23). OmcF and the c 6 family of c-type cytochromes share a 74-amino-acid domain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The c 6 cytochromes serve as electron donors to cytochrome c oxidase in cyanobacteria (2, 13) and transfer electrons from cytochrome b 6 f to photosystem I in both cyanobacteria and unicellular algae (2,13,23). OmcF and the c 6 family of c-type cytochromes share a 74-amino-acid domain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The similarity of OmcF to cytochrome c 6 of cyanobacteria and planktonic algae suggests that it may serve as an important electron carrier in G. sulfurreducens (2,13,23). If OmcF is part of a complex with one or more of the cytochromes that were not present in the OmcF-deficient mutant, then the absence of OmcF might result in accumulation of partially folded components of the complex, which, as seen in E. coli (44)(45)(46)59), could activate an envelope stress response influencing gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of isiAB by other stresses in the presence of iron is intriguing, because it had been suggested that Fur, a transcription repressor with iron as co-factor, was involved in the repression of isiAB transcription. Elevated transcription of the isiAB operon now has been seen under heat or salt stress (Vinnemeier et al 1998;Vinnemeier and Hagemann 1999;Geiss et al 2001a, b); in some cyanobacterial mutants, such as in a cytochrome c 6 -deficient Synechocystis mutant (Ardelean et al 2002) and a PsaJFfree Synechocystis mutant (Jeanjean et al 2003); under peroxide stress ); under high light (Havaux et al 2005) and during light-limited growth (Foster et al 2006). Unfortunately, not all studies provided evidence that de-repression of isiAB transcription is accompanied by protein synthesis and membrane integration of IsiA.…”
Section: Characteristics Of the Isia Proteinmentioning
confidence: 99%
“…Recently, some investigations at the transcriptional level have shown that expression of the isiA gene can be induced in conditions other than iron-deficiency. IsiA expression has been characterised under oxidative stress under iron replete conditions (Yousef et al 2003;Michel and Pistorius 2004) and, the transcription of the isiA gene is also observed in some cyanobacterial mutants, such as a cytochrome c 6 -deficient mutant (Ardelean et al 2002) and a psaFJ null mutant of Synechocystis sp. PCC 6803 (Jeanjean et al 2003).…”
Section: Iron Stress In Cyanobacteriamentioning
confidence: 99%